A simple method for conidial production and for inoculating apples with Neofabraea alba - Pushparajah, I.P.S.; Fisher, B.M.; Wood, P.N.; Everett, K.R. (New Zealand Plant Protection, 2016)
Current methods for producing conidia of Neofabraea alba the fungal cause of Bulls eye rot of apple are laborious and timeconsuming A minimum of 6 weeks is required Mycelial cultures of N alba did not produce conidia on commonly used potato dextrose agar and therefore several other media were tested Growth on corn meal agar resulted in a high conidial yield (ca 106 conidia/ml) after 57 days growth Published research reports a method to inoculate apples with this pathogen without wounding but it requires specialised equipment A simple method that does not require specialised equipment was developed to inoculate apple fruit with the Bulls eye rot pathogen without wounding Conidia were placed on water agar and apple fruit were placed on these spores for at least 5 days for establishment of infections Reliable infection of 7080 of apples required a 14day wetness period after the fruit were placed on the conidial solution This woundfree N alba inoculation method provides the basis for further research to examine the effect of various treatments designed to reduce the impact of this pathogen in apple orchards